Iowa Birdline update, January 14, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for January 14, 1994. Highlights include Smith's Longspur, Snowy Owl, and a Varied Thrush. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed